In situ engineered triple phase boundary enhancement in 3D structured carbon supported catalyst for high-temperature PEMFC - Pandikassala, Ajmal; Jadhav, Swapnil D.; Kurian, Maria; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2025)
Enhancing platinum (Pt) utilization in polymer electrolyte membrane fuel cells (PEMFCs) requires optimizing the catalyst support microstructures to expand the triple-phase boundary (TPB). A promising method has been reported here which employs a three-dimensional (3D) catalyst support with an in situ-generated ionomer interface from preadmitted monomer molecules, potentially replacing the traditional Nafion ionomers. The small-sized monomers infiltrate the catalyst's pores, and UV curing polymerizes them into an extended interfacial network within the 3D carbon support. The single-cell analysis of the membrane electrode assemblies (MEAs) in high-temperature PEMFCs (HT-PEMFCs) using phosphoric acid-doped polybenzimidazole (PBI) membranes highlights the effectiveness of this approach. The strategy helps to achieve a current density of 1.06 A cm-2 and 0.49 A cm-2 at 0.60 V in H2-O2 and H2-air feed conditions, respectively. These values represent a significant improvement over the conventional Nafion ionomer-based MEAs, which exhibit current densities of 0.87 A cm-2 and 0.40 A cm-2 under H2-O2 and H2-air feeds, respectively, when utilizing a platinum-supported carbon (Pt/C) catalyst. When Pt nanoparticles are decorated on a high-surface-area, porous 3D interconnected carbon support synthesized via the carbonization of the polydopamine-coated melamine foam (Pt/3DPDC), the conventional Nafion ionomers tend to block the nanopores in the 3D carbon supports, leading to the underutilization of the Pt active sites. In contrast, the in situ ionomer approach enabled the system to deliver 0.93 A cm-2 at 0.60 V H2-O2 feed conditions, which is significantly higher than 0.38 A cm-2 obtained with the Nafion-based ionomers under similar conditions. This approach successfully makes use of the Pt active sites present in the nanopores and tackles the issues of mass transfer and reactant distribution, both of which are essential for expanding fuel cells from single cells to stacks. The exhibited method emphasizes how crucial it is to develop process-friendly electrocatalysts and complementary electrode manufacturing techniques in order to advance the PEMFC performance through a novel scientific path.